Rubella and Congenital Rubella Syndrome in the Philippines: A Systematic Review - Anna Lena Lopez; Peter Francis N. Raguindin; Maria Asuncion Silvestre; Xenia Cathrine J. Fabay; Ariel B. Vinarao; Ricardo Manalastas (International Journal of Pediatrics)
Background. As part of regional elimination efforts, rubella-containing vaccines (RCV) have recently been introduced in the Philippines, yet the true burden of rubella and congenital rubella syndrome (CRS) in the country is largely unknown. Objective. To provide baseline information on rubella and CRS prior to routine vaccine introduction in the Philippines. Methods. We conducted a systematic literature review on rubella and CRS in the Philippines, including a cross-sectional study conducted in 2002 among 383 pregnant women attending the obstetric outpatient clinic of the Philippine General Hospital to assess rubella susceptibility of women of childbearing age. Results. 15 locally published and unpublished studies were reviewed. Susceptibility to rubella among women of childbearing age was higher in rural communities. Retrospective reviews revealed congenital heart diseases, cataracts, and hearing impairments to be most common presentations in children of CRS. In the cross-sectional study, 59 (15.4%) of the 383 pregnant women enrolled were seronegative for rubella IgG. Conclusion. Similar to other countries introducing RCV, it was only recently that surveillance for rubella has been established. Previous studies show substantial disabilities due to CRS and a substantial proportion of susceptible women who are at risk for having babies affected with CRS. Establishment of CRS surveillance and enhanced awareness on rubella case detection should be prioritized.